Acute injuries in male elite ice hockey players. A prospective cohort study - Hirvelä, J.; Tuominen, M.; Airaksinen, O.; Hänninen, T.; Lindblad, N.; Ryhänen, H.; Tikanto, J.; Parkkari, J. (Journal of Science and Medicine in Sport Plus, 2024)
Background In Finland, elite level ice hockey injury studies have not been conducted since 1990s. Epidemiological data is needed for developing injury prevention. The aim of this study was to calculate the injury incidences and to describe details of the injuries in the men's elite-level ice hockey league in Finland (Liiga).